Effectiveness of Ethnoscience-Based Creative Problem Solving Learning Model on Problem-Solving Abilities - Islami, Annisa Latifah Nur; Faizah, Ulinnuha Nur (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
Problem-solving ability is a skill that requires thinking by using and connecting with various rules that we already know that are important for students to have. This study aims to determine the effectiveness of the ethnoscience-based creative problem-solving learning model on the problem-solving abilities of sixth-grade students at MIN 2 Ponorogo. This study was designed using a quantitative research method with an experimental research type. While the research design is Quasi Experimental Design. The sample used was 21 students of class VI MIN 2 Ponorogo as the experimental class sample and 23 students as the control class sample. Data collection was carried out by observation and tests. The research data were then analyzed using the T test, N-Gain test, and Cohen's Effect Size test. The problem-solving abilities of students who applied the ethnoscience-based creative problem-solving learning model were different when compared to the problem-solving abilities of students who applied the conventional learning model. Based on the calculation of the two-tailed t test, it was found that the sig. (2 tailed) 0.000 and the value is less than 0.05, and the one tailed t test can be seen that the significance value is 0.00 and the value is less than 0.05, so it can be concluded that H0 is rejected and H1 is accepted. Therefore, it can be said that the problem-solving ability of students in the experimental class with the ethnoscience-based creative problem-solving learning model is better than the problem-solving ability of students in the control class.